1998
DOI: 10.1152/ajpgi.1998.274.1.g52
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in multiple steps in hepatic transport of palmitate support a balanced uptake mechanism

Abstract: Hepatic clearance of long-chain fatty acids is substantially faster in females than in males, a fact that may underlie known gender-related differences in lipoprotein metabolism and associated disease states. To further investigate the transport steps responsible for this difference, we used a novel method combining multiple-indicator dilution and steady-state measurements of palmitate extraction from albumin solutions. We found that cytoplasmic transport of palmitate is sufficiently slow (diffusion constants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
19
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…The first is the long-recognized difference in long chain fatty acid uptake and utilization in the livers of male and female rats (Ockner et al, 1979). There is no explanation of this difference that is wholly satisfactory, either in terms of the known plasma membrane fatty acid binding protein (FABPpm) or cytosolic fatty acid binding protein (Luxon et al, 1998;Sorrentino et al, 1992). The second is the difference between men and premenopausal women with respect to both blood cholesterol levels and the incidence of cholesterol-associated diseases (Anderson et al, 1987;Barker et al, 1979;Simons, 1986).…”
Section: Zhang Et Almentioning
confidence: 99%
“…The first is the long-recognized difference in long chain fatty acid uptake and utilization in the livers of male and female rats (Ockner et al, 1979). There is no explanation of this difference that is wholly satisfactory, either in terms of the known plasma membrane fatty acid binding protein (FABPpm) or cytosolic fatty acid binding protein (Luxon et al, 1998;Sorrentino et al, 1992). The second is the difference between men and premenopausal women with respect to both blood cholesterol levels and the incidence of cholesterol-associated diseases (Anderson et al, 1987;Barker et al, 1979;Simons, 1986).…”
Section: Zhang Et Almentioning
confidence: 99%
“…L-FABP levels are known to be gender dependent, with females showing higher levels than males (25). L-FABP is also altered in various conditions, such as pregnancy and clofibrate treatment (6,26,31).…”
mentioning
confidence: 99%
“…For example, liver cells contain Ͼ10 m 2 of membranes per cubic centimeter of volume (4), sufficient to bind the vast majority of unesterified fatty acid molecules in the cytoplasm (20). Yet, hepatocytes efficiently transfer fatty acids from the plasma membrane to intracellular sites of metabolism (16,20).…”
mentioning
confidence: 99%
“…More than 20 years ago, Tipping and Ketterer (32) proposed that soluble binding proteins may stim-ulate cytoplasmic transport of their ligands by increasing their aqueous solubility. FABP has been shown to stimulate intracellular fatty acid mobility in cultured cells (18,20,22,23), perfused rat liver (16,19), and artificial cytoplasm (29,38), whereas knock out of the gene for heart FABP was found to greatly impair cardiac fatty acid metabolism (3). Weisiger and co-workers (15,16,20) have shown that the rate of fatty acid diffusion within liver cells is directly proportional to the concentration of liver FABP, and they have proposed that soluble binding proteins act as an aqueous carrier system that reduces binding of fatty acids and other molecules to immobile cytoplasmic membranes (20,37).…”
mentioning
confidence: 99%
See 1 more Smart Citation